14,001 views

2 Answers

Best answer
12 votes
12 votes
To prove the equivalence of two regular expressions , we should try to reduce one r.e. into r.e using identities which we have or using proper reductions.For understanding proper reduction , let us understand by a simple example first :

We know (r* + s*)* = (r*s*)* = (r + s)*.But we have to know how it is true.For that let us the equality between 1st and 2nd terms:

In (r*s*)* , if we keep s* = ϵ , so we obtain r*.

Similarly by keeping r* = ϵ , we obtain s*.

So we can take either any combination of combination of r* and s*

Hence (r*s*)* = (r* + s*)*

Similarly taking r from r* and s from s* we get : (r* + s*)* = (r + s)*

 

Now on the similar approach lets solve the given query :

LHS = (a*ab + ba)* a*

Let r1 = (a*ab + ba)* and r2 = a*

Keeping a* = ϵ , we obtain the LHS term as : (ab + ba)*..This is one case

Now let r1 = ϵ , so r1* = ϵ , hence LHS term is reduced to : a*

 

Hence the overall expression considering the above 2 cases can be briefed as : (a + ab + ba)* since (ab + ba)* is already obtained in the 1st case and using the 2nd term we get any combination  of 'a' and hence it can be  inside (a + ab + ba)*

 

Hence the two expressions given are equivalent
selected by

Related questions

2 votes
2 votes
0 answers
1
set2018 asked Aug 15, 2017
1,239 views
1 votes
1 votes
1 answer
3
0 votes
0 votes
1 answer
4
Sourav_35 asked Mar 15, 2018
2,223 views
Construct a DFA such that it accepts all strings over $\{a,b\}$ in which there are at least two occurrences of $b$ between any two occurrences of $a$.